2006
DOI: 10.1038/sj.bjp.0706451
|View full text |Cite
|
Sign up to set email alerts
|

In vivo release of non‐neuronal acetylcholine from the human skin as measured by dermal microdialysis: effect of botulinum toxin

Abstract: 1 Acetylcholine is synthesized in the majority of non-neuronal cells, for example in human skin. In the present experiments, the in vivo release of acetylcholine was measured by dermal microdialysis. 2 Two microdialysis membranes were inserted intradermally at the medial shank of volunteers. Physiological saline containing 1 mM neostigmine was perfused at a constant rate of 4 ml min À1 and the effluent was collected in six subsequent 20 min periods. Acetylcholine was measured by high-pressure liquid chromatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 18 publications
1
40
0
Order By: Relevance
“…The involvement of mediatophore in acetylcholine release from T cells has also been proposed [2]. However, microdialysis experiments on human skin suggested that other transporters should also be involved in non-neuronal acetylcholine release [19]. More recently human OCTN1 has been found to be competent for acetylcholine transport [16,17].…”
Section: Introductionmentioning
confidence: 97%
“…The involvement of mediatophore in acetylcholine release from T cells has also been proposed [2]. However, microdialysis experiments on human skin suggested that other transporters should also be involved in non-neuronal acetylcholine release [19]. More recently human OCTN1 has been found to be competent for acetylcholine transport [16,17].…”
Section: Introductionmentioning
confidence: 97%
“…The role of acetylcholine as an important regulator of sweating is well explored (721)(722)(723) (see also Table 2). In contrast, the exact role of autonomic nerve-derived neuropeptides such as CGRP, VIP, and galanin, for example, is only poorly understood (160, 341,558,574).…”
Section: Neuroanatomy and Neurophysiology Of Autonomic Nervesmentioning
confidence: 99%
“…However, emerging evidence indicates that normal and neoplastic nonneuronal cells also produce and release ACh. Strong evidence for nonneuronal ACh production is reported in human keratinocytes and small cell lung cancer cells (7,20,24), indicating in these tissues that ACh may act as an autocrine or paracrine growth factor. Likewise, ACh production by spermatozoa (19), parotid gland epithelium (11), human vascular endothelium (12), and small intestinal mucosa (27) is suggested.…”
mentioning
confidence: 99%